Pengaruh Model Kooperatif Think Pair Share Terhadap Hasil Belajar PKn Siswa Kelas V Sekolah Dasar - Fitria Abadi; Zuardi Zuardi; Zainarlis Zainarilis (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
Research this aiming for knowing influence of cooperative models Think Pair Share to the results learn PKn class V SDN Gugus I Subdistrict Sungai Pua districts Agam . Research this is research quantitative with method research experiment . Sample on research this composed from two group , i.e. group experiment totaling 20 students and group control which amounted to 20 students , with total population as many as 122 people. Instruments used in collect data ie in the form of test with type selection double . Results research that has analyzed , obtained t count > t table namely 2,625> 1 , 68595 with α = 0.05 which means Ho is rejected and Ha is accepted . So that could concluded there is influence of cooperative models Think Pair Share ( TPS ) against the results learn PKn class V SDN Gugus I Subdistrict Sungai Pua districts Agam .                                                                                                  keywords: think pair share ( tps ) model , pkn